A particle-element contact algorithm incorporated into the coupling methods of FEM-ISPH and FEM-WCSPH for FSI problems - Long, Ting; Hu, Dean; Yang, Gang; Wan, Detao (Ocean engineering, 2016)
Numerical simulation of FSI problems is one of the most important topics in computational fluid dynamics. In this paper, a particle-element contact algorithm is incorporated into coupling methods of FEM-ISPH and FEM-WCSPH for solving FSI problems. The objective of contact algorithm is to adjust positions and normal velocities of slave particles and master nodes by conservation of linear momentum and angular momentum. Compared with particle–particle contact algorithm, which is based on contact force of Monaghan boundary condition, the calculation of contact force is not required in the present contact algorithm. Moreover, correction algorithms of Yildiz et al. are used for both WCSPH and ISPH to treat noises in fluid field and improve the accuracy of numerical simulations. Numerical examples investigate the comparison of particle-element contact algorithm and commonly used particle–particle contact algorithm, and it indicates that the present contact algorithm is effective for FSI problems. •A particle-element contact algorithm is simplified and incorporated into coupling methods of FEM-ISPH and FEM-WCSPH.•The calculation of contact force is not required in the present contact algorithm.•Comparison of the present contact algorithm and commonly used particle–particle contact algorithm is investigated.•Numerical examples indicate that the present contact algorithm is effective and accurate for FSI problems.